2015
DOI: 10.1007/s10342-015-0891-1
|View full text |Cite
|
Sign up to set email alerts
|

Foliar nutrient resorption constrains soil nutrient transformations under two native oak species in a temperate deciduous forest in Mexico

Abstract: Foliar nutrient resorption (FNR) is a key process in the dynamics of nutrients in a forest ecosystem. Along with other factors, FNR regulates the chemical composition of the forest floor and, consequently, the rates of organic matter decomposition and soil nutrient availability. The main objective of the present study was to examine the effect of FNR of two deciduous oak species (Quercus castanea and Q. deserticola) in the litter and soil nutrient dynamics, in addition to analyze whether the interaction betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 91 publications
(112 reference statements)
0
17
0
2
Order By: Relevance
“…Co-occurring oaks may facilitate (or benefit) each other more than has been recognized (Callaway et al, 2002). Shade and fine-root dynamics of incumbent oaks may facilitate colonization of other oak species by preventing grasses from establishing (Callaway et al, 1991;Callaway & Davis, 1998) or by enhancing soil conditions (Chavez-Vergara et al, 2015). For example, oak species with low nutrient resorption in leaves may improve soil fertility, benefitting oaks with high nutrient resorption.…”
Section: Reviewmentioning
confidence: 99%
“…Co-occurring oaks may facilitate (or benefit) each other more than has been recognized (Callaway et al, 2002). Shade and fine-root dynamics of incumbent oaks may facilitate colonization of other oak species by preventing grasses from establishing (Callaway et al, 1991;Callaway & Davis, 1998) or by enhancing soil conditions (Chavez-Vergara et al, 2015). For example, oak species with low nutrient resorption in leaves may improve soil fertility, benefitting oaks with high nutrient resorption.…”
Section: Reviewmentioning
confidence: 99%
“…It has been shown that when more than two species inhabit the same area, the community of microorganisms increments its abundance and activity promoting higher soil nutrient availability (Gartner and Cardon, 2004). Therein, a recent study found that Quercus deserticola benefits Q. castanea by incorporating nutrients to the soil and facilitating the decomposition of litter (Chávez-Vergara and García-Oliva 2013; Chávez-Vergara et al 2014;2015). Overall, this complementarity effects might promote coexistence.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was detected that the association of two oak species produce higher nutrient availability, which resulted advantageous for one of the species (Chávez-Vergara et al 2014;2015). Although, this exhibited the benefits of species coexistence, the evidence supporting the frequency of the associations between oak species is still scant.…”
Section: Patrones De Distribución De Nueve Especies De Quercus a Lo Lmentioning
confidence: 99%
See 2 more Smart Citations